Using Kotter’s theory to lead change at University of Khartoum: A qualitative study - Saifaldin Idris Onia (Universitas Negeri Yogyakarta, 2022)
Changes in Universities need to be prepared, enforced, and sustained to turn the universities into institutions that can function effectively and efficiently. Kotter’s change model is one of the most widely recognised models for leading change, and yet there are few case studies have been used this model in the academic literature. Therefore, this study aimed to test Kotter’s change model at University of Khartoum. To do so, a qualitative research design was followed. To collect data a semi-structured interview was used with 11 leaders in the University of Khartoum. The thematic analysis has shown that create an environment for change depends on create urgency, and develop a vision for change that convinces staff members to participate in the change process. It is evident that the University of Khartoum has engaged and enabled the staff members in each college and work unit to embrace the change. Besides, the analysis indicated that for the change to be implemented and sustained it needs to removing obstacles and making it the university culture. The paper recommended that the importance of change must be embedded in the vision of the University of Khartoum to create a strong climate for change in the University environment.